Swinging the pendulum: lessons learned from public discourse concerning hydroxychloroquine and COVID-19. (2nd July 2020) - Sattui, Sebastian E.; Liew, Jean W.; Graef, Elizabeth R.; Coler-Reilly, Ariella; Berenbaum, Francis; Duarte-García, Alí; Harrison, Carly; Konig, Maximilian F.; Korsten, Peter; Putman, Michael S.; Robinson, Philip C.; Sirotich, Emily; et al.
ABSTRACT: Introduction: Several months into the COVID-19 pandemic, safe and effective treatments against this global health disaster have yet to be identified. Clinical research trials around the world are underway testing a wide array of possible medications. In particular, the off-label use of hydroxychloroquine for COVID-19 prophylaxis and treatment has created many unprecedented challenges for the scientific community and the public. Areas covered: We critically assessed major events from February – May 2020 that contributed to widespread use of hydroxychloroquine for the treatment and prophylaxis of COVID-19. We aimed to explore how opinions toward hydroxychloroquine may shift from early enthusiasm (based on in vitro and preliminary clinical data) to the hope for a miracle cure (through communication and promotion of questionable results) and, finally, to a rise of skepticism as more in-depth analyses are emerging. Expert opinion: Mindful and rigorous acquisition of data, as well as its interpretation, are essential to an effective pandemic response. The rapid and premature promotion of results has had major implications for global crisis management, even creating distrust among the public. It is crucial for the medical and scientific community to incorporate the lessons learned from this situation.